Scientific report local practicies of land grouping in the red river delta aiming at increasing the efficiency of agricultural land (Nhà xuất bản Hà Nội, 2004)
Contents: Overall review; research objective and research methodology; research result; advantage and disadvantage in land grouping with authority's intervention.